CHA2DS2 - Vasc Score Predict No Reflow Phenomenon in Primary Percutaneous Coronary Intervention - Eldarky, Elsayed Abd Elkhalek; Elkeshk, Eman Saied; Elnager, Amr Elsayed; Soliman, Mikel Magdy Selim (American Journal of Health, Medicine and Nursing Practice, 2023)
Purpose: ST-Elevation Myocardial Infarction is the most acute manifestation of Coronary artery disease, with substantial morbidity and mortality. Early reperfusion (re-establishing the blood flow in the occluded artery) is the most effective way to preserve the viability of the ischaemic myocardium and limit infarct size. Early diagnosis of STEMI is crucial to initiate appropriate treatment and should ideally be made within 10"‰minutes of first medical contact. This study aimed to evaluate the CHA2DS2-VASc score as a simple tool for predicting the no-reflow among patients with STEMI who underwent primary percutaneous coronary intervention. Methodology: This was a case-control study which was conducted on 100 patients, diagnosed with acute STEMI and underwent primary PCI, who was admitted to Cardiology Department, Benha University Hospital and National Heart Institute. Patients were classified into two groups, control and no-flow, according to their final angiographic TIMI flow rates resulting from primary PCI. The control group: 78 patients with TIMI flow rate >2. The no-reflow group: 22 patients with TIMI flow rate â‰¤2, despite mechanical reopening of the infarct-related artery in patients without dissection of the coronary artery. Findings: In this study, LVEF was significantly lower in patients with no-reflow compared to patients with normal TIMI flow (p <0.001), but LVEDV was significantly higher (p =0.01). There was no significant difference in LVESV between patients with no-reflow compared to patients with normal TIMI flow. CHA2DS2VASC score was significantly higher in patients with no-reflow compared to patients with normal TIMI flow (p <0.001). CHA2DS2VASC score is a significant predictor of occurrence of no reflow phenomenon (AUC: 0.689, p =0.006). At a cut off value of â‰¥ 2it has a sensitivity of 68.2%, specificity of 58.9%, PPV of 31.9% and NPV of 86.8%. Recommendation: The study suggest that the CHA2DS2"‘VASc score can be an independent predictor of no"‘reflow phenomenon in patients undergoing primary PCI. As a simple and easy"‘to"‘calculate score, it might be a useful assessment tool to predict no"‘reflow phenomenon before primary PCI interventions in patients with STEMI. Thus we recommend using CHA2DS2-VASc score as it is very simple and a quick tool to predict no-reflow before primary PCI